2009
DOI: 10.1007/s00449-009-0338-5
|View full text |Cite
|
Sign up to set email alerts
|

The use of additives as the stimulator on mycelial biomass and exopolysaccharide productions in submerged culture of Grifola umbellata

Abstract: In this study, various additives including organic acids, alcohols, vegetable oils, surfactants and polymers were added in the cultural medium to investigate their stimulatory effects on Grifola umbellate mycelia growth and exopolysaccharide (EPS) production. It was found that the commonly used stimulatory additives, effective in other mushrooms' cultures, exhibited negative results in Grifola umbellata submerged culture. In contrast, the polymer additive, polyethylene glycol (PEG), displayed an effective stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…Plant oils and fatty acids have been successfully employed to enhance EPS production [34]. Fatty acid, oils, surfactants, and polymers have been reported to promote the production of fungal metabolites [35,36]. However, no attempt has been made with regard to the use of organic solvents under submerged cultivation of A. luteo-virens Sacc QH.…”
Section: Effect Of Additives On Mycelial Growth and Eps Productionmentioning
confidence: 98%
See 1 more Smart Citation
“…Plant oils and fatty acids have been successfully employed to enhance EPS production [34]. Fatty acid, oils, surfactants, and polymers have been reported to promote the production of fungal metabolites [35,36]. However, no attempt has been made with regard to the use of organic solvents under submerged cultivation of A. luteo-virens Sacc QH.…”
Section: Effect Of Additives On Mycelial Growth and Eps Productionmentioning
confidence: 98%
“…It is likely that high concentrations of surfactant can lead to the damaged effect on cell morphology structure and metabolism. Chen et al [36] find that the polymer additive, polyethylene glycol (PEG), displayed an effective stimulatory effect on both biomass and EPS productions in Grifola umbellata submerged culture. Choi et al [37] report the increased effect of microbial metabolites production by several stimulating agents, which include fatty acids, surfactants, vegetable oils, and organic solvents.…”
Section: Effect Of Additives On Mycelial Growth and Eps Productionmentioning
confidence: 99%
“…Hence, the surfactants might partially be incorporated into the fungal cell membrane thereby increasing the uptake efficiency of nutrients from the culture medium. In this way, nutrient absorption to cell surface can be greatly enhanced through the aid of surfactants [21,30]. Tween 80 affected mass transfer by changing composition in P. tuber-regium mycelial cell membrane and significantly increased the glucose consumption rate [22].…”
Section: Effects Of Surfactantsmentioning
confidence: 98%
“…The EPS is one of the most desired products in submerged cultivation of G. frondosa , and it has become a hot topic to obtain EPS of G. frondosa in maximum amount in recent years (Hsieh et al ., , ). Meanwhile, to accelerate biomass (BIO) and EPS productions, many studies in recent years have shown that proper amount of additives as the stimulator was added into the fungal culture can significantly promote fungal growth and increase the biosynthesis of EPS (Tang & Zhong, ; Liu & Zhang, ; Chen & Huang, ).…”
Section: Introductionmentioning
confidence: 99%